A incorporação da Agenda 2030 na Embrapa: efeitos nas atividades desenvolvidas nos bancos de sementes ex situ - Damasceno, Jéssica Viani (2022)
The United Nations’ 2030 Agenda is an action plan to implement the 17 Sustainable Development Goals (SDGs) and the 169 to be achieved by 2030. The objective of this research is to analyze how the process of incorporation of the 2030 Agenda in Embrapa happens and to evaluate if it promoted effects in the activities carried out in the scope of the ex situ seed banks. For this, documentary and bibliographic research and semi-structured interviews were carried out, mobilizing the concept of incorporation and its levels of analysis, defined by Galvão and Ramiro (2022). From this, it is concluded that even if it is possible to identify the organization’s involvement with the SDGs, when specifically addressing the seed banks, no changes are identified in the issues related to it.